Clinical utility of third‐trimester uterine artery Doppler in the prediction of brain hemodynamic deterioration and adverse perinatal outcome in small‐for‐gestational‐age fetuses. (27th January 2015) - Cruz‐Martinez, R.; Savchev, S.; Cruz‐Lemini, M.; Mendez, A.; Gratacos, E.; Figueras, F.
ABSTRACT Objective To assess the clinical value of third‐trimester uterine artery (UtA) Doppler ultrasound in the prediction of hemodynamic deterioration and adverse perinatal outcome in term small‐for‐gestational‐age (SGA) fetuses. Methods UtA Doppler parameters, cerebroplacental ratio (CPR) and fetal middle cerebral artery (MCA) pulsatility index (PI) were evaluated weekly, starting from the time of SGA diagnosis until 24 h before induction of labor, in a cohort of 327 SGA fetuses with normal umbilical artery PI (< 95th centile), delivered at > 37 weeks' gestation. Differences in the sequence of CPR and MCA‐PI changes < 5th centile, between the group with normal UtA Doppler indices at diagnosis and those with abnormal UtA indices, were analyzed by survival analysis. In addition, the use of UtA Doppler value, alone or in combination with a brain Doppler scan before delivery, to predict the risk of Cesarean section, Cesarean section for non‐reassuring fetal status (NRFS), neonatal acidosis and neonatal hospitalization was evaluated by logistic regression analysis, adjusted for gestational age at birth and birth‐weight percentile. Results Abnormal UtA Doppler at diagnosis of SGA was associated with a higher risk of developing abnormal brain Doppler indices before induction of labor than in those with a normal UtA at diagnosis (62.7% vs 34.6%, respectively; P < 0.01). Compared to those with normal UtA Doppler indices, those with abnormal UtA Doppler findings were associated with a higher risk of intrapartum Cesarean section (52.2% vs 37.3%, respectively; P = 0.03), Cesarean section for NRFS (35.8% vs 23.1%, respectively; P = 0.03), neonatal acidosis (10.4% vs 7.7%, respectively; P = 0.47) and neonatal hospitalization (23.9% vs 16.5%, respectively; P = 0.16). Logistic regression analysis indicated that UtA Doppler findings were not significantly associated with adverse perinatal outcome independent of brain Doppler findings. Conclusion UtA Doppler indices predict adverse perinatal outcome, but do not help to improve the predictive value of brain Doppler indices. However, at the time of SGA diagnosis they identify the subgroup of fetuses at highest risk of progression to abnormal brain Doppler findings. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.